Protective effect of chemically modified SOD on lipid peroxidation and antioxidant status in diabetic rats - Mansuroglu, Banu; Derman, Serap; Yaba, Aylin; Kizilbey, Kadriye (ELSEVIER SCIENCE BV, 2015)
Reactive oxygen species mediated oxidative stress play an important role on the injury of tissue damage and increased attention has been focused on the role of free radicals in diabetes mellitus (DM). In the present study firstly superoxide dismutase (SOD) enzyme was chemically modified with two different polymer and physicochemical properties of these conjugates clearly analyzed. Then, the stability of carboxymethylcellulose-SOD (CMC-SOD) and poly methyl vinyl ether-co-maleic anhydride-SOD (PMVE/MA-SOD) conjugates was investigated against temperature and externally added H2O2. Moreover, we investigated the effect of chemically modified SOD enzyme on lipid peroxidation and antioxidant status in streptozotocin (STZ)-induced diabetic rats. PMVE/MA-SOD conjugate treatment significantly reduced MDA level compared with the control groups, native and CMC-SOD conjugate treated groups in brain, kidney and liver tissue. GSH and SOD enzyme activity in diabetic groups was significantly increased by treatment of CMC-SOD and PMVE/MA-SOD conjugates. The protective effects on degenerative changes in diabetic rats were also further confirmed by histopathological examination. This study provides the preventative activity of SOD-polymer conjugates against complication of oxidative stress in experimentally induced diabetic rats. These results suggest that chemically modified SOD is effective on the oxidative stress-associated disease and offer a therapeutic advantage in clinical use. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Superoxide dismutase; Chemical modification; Lipid peroxidation; Antioxidant status; SUPEROXIDE-DISMUTASE; CU,ZN-SUPEROXIDE DISMUTASE; ANTIINFLAMMATORY PROPERTIES; IN-VITRO; ACID; DELIVERY; ENZYMES; COMPLEX; INJURY; PHARMACOKINETICS; Biochemistry & Molecular Biology; Chemistry; Polymer Science